Gerakan Literasi di SDN 060936 Melalui Program Pojok Baca - Oktarin, Egidya; Siregar, Hairani; Kaloko, Nurazizah (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2025)
Literacy is a basic ability of a person who must be mastered in processing and searching for information. Literacy environment is what students need to support an environment that supports literacy programs or habituation in schools. Apply the reading corner itself can be a solution to this problem. Reading corner can be the beginning of the formation of a literacy environment in the school environment, especially in each class. In retelling students are directed to be skilled in speaking as well as doing literary appreciation. The method implemented in this service uses the intervention method in the mezzo realm. The group work method is defined as part of the intervention method because by utilizing groups as a therapy method, building interactions and relationships, and developing the potential of individuals to be able to overcome their problems through and within the group. Intervention stages carried out include engagement (approach), assessment, planning, intervention, evaluation, and termination. The analysis technique used is descriptive qualitative. The subjects in this activity were students of grades IV and V at SDN 060936 Medan Johor. The implementation of community service activities is carried out by applying a reading corner and coaching analyzing stories and retelling. Results of activities This dedication can instill in students to create and improve culture reading habits and various things related to the love of reading.